Nitrogen supply associated with rhizobacteria in the first productive cycle of Marandu grass - Sampaio, Fernando Antônio Rebouças [UNESP]; Teixeira Filho, Marcelo Carvalho Minhoto [UNESP]; da Silva Oliveira, Carlos Eduardo [UNESP]; Jalal, Arshad [UNESP]; Boleta, Eduardo Henrique Marcandalli [UNESP]; de Lima, Bruno Horschut [UNESP]; Rosa, Poliana Aparecida Leonel [UNESP]; Galindo, Fernando Shintate [UNESP]; de Souza, Jeferson Silva [UNESP] (Springer Nature, 2021)
The rhizobacteria of genus Azospirillum and Bacillus are effective at fixing atmospheric nitrogen, promote plant growth and can largely contribute to beneficial recovery from degraded pastures. This study aimed to evaluate the development and nutritional status of Urochloa brizantha cv. Marandu in response to nitrogen doses along with inoculation of Azospirillum brasilense and Bacillus subtilis. The experiment was carried in a completely randomized design in a greenhouse with four replications and in factorial scheme 4 × 5. The treatments were consisted of seeds inoculation (without inoculation, A. brasilense (strains Ab-V5, Ab-V6), B. subtilis (strain CCTB04) and co-inoculation with strains of A. brasilense + strain of B. subtilis, and nitrogen doses (0, 50, 100, 150 and 200 kg ha−1, equivalent to 0, 25, 50, 75 and 100 mg dm−3 N) from urea. The sole inoculation of A. brasilense and B. subitilis promoted plant height of Marandu grass along with nitrogen fertilization. The co-inoculation of these bacteria increased potassium accumulation in Marandu grass along with nitrogen doses. Regardless of bacterial inoculation, number of tillers, leaves, dry matter accumulation, crude protein and accumulations of N, P, Ca, S and Mg were increased with increasing nitrogen doses in the first forage cycle.
Keywords: Nitrogen biological fixation; Nutrients removal; Plant growth-promoting bacteria; Recovery of degraded pastures; Shoot dry mass